2007
DOI: 10.1248/bpb.30.791
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Metallothionein Synthesis by Cilostazol in Mice and in Human Cultured Neuronal Cell Lines

Abstract: Cilostazol, a quinolinone derivative, is approved by the Food and Drug Administration for the treatment of intermittent claudication.1) It has been shown that Cilostazol has an inhibitory effect on platelet aggregation and thronbosis in feline cerebral ischemia.2) Cilostazol has also been shown to significantly reduce the risk of recurrent strokes without affecting the occurrence of intracranial hemorrhage. Recently, the Cilostazol Stroke Prevention Study revealed that Cilostazol reduced the risk of secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(12 reference statements)
2
7
0
Order By: Relevance
“…It is well known that zinc protects against Cd toxicity through the induction of MT synthesis in various systems (Leber and Miya, 1976;Goering and Klaassen, 1984). Recent observations, including our reports, using human vascular endothelial cells have demonstrated that cilostazol, as well as Cd and iAs III , induces MT synthesis (Suzuki et al, 2007;Fujiwara et al, 2009Fujiwara et al, , 2010Fujiwara et al, and 2011. The present study also showed that cilostazol induced MT mRNA and protein levels in bovine aortic endothelial cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is well known that zinc protects against Cd toxicity through the induction of MT synthesis in various systems (Leber and Miya, 1976;Goering and Klaassen, 1984). Recent observations, including our reports, using human vascular endothelial cells have demonstrated that cilostazol, as well as Cd and iAs III , induces MT synthesis (Suzuki et al, 2007;Fujiwara et al, 2009Fujiwara et al, , 2010Fujiwara et al, and 2011. The present study also showed that cilostazol induced MT mRNA and protein levels in bovine aortic endothelial cells.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, several studies have demonstrated that cilostazol induces MT synthesis in not only vascular endothelial cells but also mouse tissues, such as the brain and liver, and cultured human cells, such as IMR32 neuroblastoma cells, coronary artery smooth muscle cells and colon carcinoma Caco-2 cells (Wakida et al, 2006;Suzuki et al, 2007;Fujiwara et al, 2009). These findings suggest that cilostazol non-specifically induces MT synthesis in various tissues and cell types.…”
Section: Discussionmentioning
confidence: 95%
“…Carey et al [28] also found induction of the MT synthesis upon the action of a lipopolysaccharide that can be released in abortions and upon the action of teratogenic factors. The metabolism of MTs is very sensitive to humoral/hormonal regulation realized via the action of glucocorticoids, catecholamines, glucagon, steroids, interleukin-6, angiotensin-2, 2-butyl cAMP and phorbol ester, as wee as of stressor factors (proteins of an acute stress phase), and other mediators [29][30][31][32][33][34][35].…”
Section: Regulation Of Mt Metabolismmentioning
confidence: 99%
“…Several antibodies to MT-3 have been reported for immunohistochemical staining (Uchida et al, 1991;Yanagitani et al, 1999;Pang and Ru, 2005), but an ELISA method which is able to determine the MT-3 concentration in clinical and/or experimental specimens has not been reported yet. Therefore, we have developed an ELISA method which may serve as an effective tool for MT-3 research and diagnostic purpose, together with mRNA quantification by RT-PCR (Tsuji et al, 1992;Pang and Ru, 2005;Suzuki et al, 2007;Hozumi et al, 2008;Honda et al, 2010). Most of the MT-3 research has been reported only by mRNA expressions without quantitative protein analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of MT-3, mRNA measurement by RT-PCR (Erickson et al, 1997;Somji et al, 2004;Suzuki et al, 2007;Haung et al, 2001) and an immunohistochemical staining method using specific antibodies (Uchida et al, 1991;Yanagitani et al, 1999;Pang and Ru, 2005) have been reported. However, a quantitative Determination of metallothionein-3 by a competitive enzyme-linked immunosorbent assay in experimental animals determination by RIA or ELISA has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%